Pendekatan IstishlÄhi dalam Ijtihad Abu Bakar Al-Shiddiq - Ikromi, Zul (IAIN Samarinda, 2017)
Abstract:This article discusses how one of the most important figures in the history of Islam, the Caliph Abu Bakr al-shiddiq, solved the problem of Islamic law. As a literature-based study, this article focuses on solving legal issues that have no implicit basis in the Qur'an because of the different times between the life of the Prophet Muhammad and the Caliph Abu Bakr as-Siddiq. It then attempts to analyze the method of ijtihad employed by Abu Bakr as-Siddiq. This article has significance in assessing methods of resolving contemporary legal problems that have no legal basis found in the source of Sharia especially in the Qurâ€™an. This study is certainly relevant to the present conditions which have different circumstances compared to that of when the Qur'an was first revealed. It thus reveals that Abu Bakr al-Siddiq used the istishlÄhi (consideration of public welfare) approach, which makes the mashlahat (public welfare) a reference in the knowing the Godâ€™s law on a human act (ijtihad). The mashlahat approach adopted by Abu Bakr al-Siddiq guided by the general spirit of the text of the Qur'an and the traditions of Prophet Muhammad. In addition, this mashlahat approach also comes from other ijtihad methods such as ijmÄ', qiyÄs and mashlahah mursalah. The ishtishlahi approach in ijtihad Abu Bakr as-Siddiq can be seen in the case of possibility of collecting the Koran, the establishment of financial and judicial institutions, fighting the apostates and anti-zakat. In such cases, it is concluded that ijtihad cannot be performed by one method alone; it takes many approaches that ultimately leads to the consideration of public benefits.Keywords: IstishlÄhÄ« approach, ijtihad, Abu Bakar al-ShiddiqÂ